Original Article Regular physical activity may influence stress hormone cortisol in Wistar rats - Arbnore Ibrahimaj Gashi , Vujica Zivkovic, Icko Gjorgoski, Seryozha Gontarev , Arjeta Azemi (Physical Education and Sport Faculty, 2020)
Engaging in regular physical activity is one of the best ways to improve overall health. Physical activity can produce differences in neural and endocrine systems. However, it is challenging to promote regular physical activity in a population that is predominantly sedentary. Therefore, exercise protocols are used to rehabilitate patients with chronic musculoskeletal conditions, cardiorespiratory and mood disorders. The aim of this study was to observe differences in hormonal status after regular aerobic physical activity for 1-7 d. This in vivo experiment analyzes the impact of physical stress on the level of cortisol. A total of 20 Wistar rats were divided into 2 groups of 10 animals per group (i.e., the-control group, and the group of rats that was subjected to the forced swim test for 7 d. On the 1st and 7th day of the experiment, blood was taken from animals in order to determine the level of cortisol using the Mouse/Rat Cortisol ELISA protocol. Our results showed that by inducing physical stress for 1-7 d on the rats, their cortisol levels decreased. The results showed that regular aerobic activity for 7 d (i.e., 60-90 min of swimming) had a positive impact on lowering the levels of stress hormone cortisol.
Keywords: cortisol, aerobic activity, physical stress, rats